EVALUATION IT GOVERNANCE COMPUTER NETWORK AT CENTRAL BUREAU OF STATISTICS (BPS) MALUKU PROVINCE USING COBIT 2019 DSS01 AND DSS05 DOMAINS - Radjulan, Juins Carlo; Iriani, Ade; Tambotoh, Johan (PATTIMURA UNIVERSITY, 2024)
This research aims to evaluate IT governance on the capability maturity level of computer networks at BPS Maluku Province using the COBIT 2019 Framework focusing on the DSS domain, namely DSS01 and DSS05. The research method uses qualitative and quantitative approaches by observing research objects, conducting interviews, and collecting data using a questionnaire distributed to the Maluku Province BPS office environment using saturation sampling techniques. The stages of this research were adapted to the COBIT 2019 framework. This research was measured using a Likert scale and utilized script apps, Google Cloud Platform, which was integrated with a web-based programming language. The results of this research show that the maturity level or capability maturity level in the DSS domain, namely the DSS01 subdomain, is 3.48 with a percentage of 69.70%. DSS05 is 3.47, with a rate of 69.47%. These two subdomains are still in the established process, level 3 with a GAP value of 2 for capability maturity level and the DSS01 domain GAP percentage of 30.30%. The DSS05 percentage is 30.53%, with a primarily achieved scale. Hopefully, this research will become a reference for improvements to several aspects that have been assessed and recommended so that computer network governance for services and activities at BPS Maluku Province becomes better.